Magnetometers Fundamentals and Applications of Magnetism - Curilef, Sergio (IntechOpen, 2020)
The stars as well as the Earth and its defects, materials, and gases have magnetic fields. To measure these fields, magnetometers are used. This book includes contributions from a variety of experts that examine the typical properties, uses, novel developments, and calibration of sensing magnetic devices. Chapters cover topics related to recent advances in the modeling and application of magnetometers.